Content Analysis of First Grade English Student's Textbook - Alawiyah, Farihatul; Ambarwati, Evi Karlina (Universitas Pahlawan Tuanku Tambusai, 2023)
Textbooks are one of the supports in teaching-learning process used as learning media in EYL classroom. As a teaching material, of course, it needs to be in accordance with the standards for textbooks writing so that it is suitable for use. But in reality, there areÂ still textbooks that are not in accordance with these standards. The aim of this research is to determine the content feasibility of textbook based on Badan Standar Nasional Pendidikan (BSNP). The research subject was an English textbooks entitled